PENGARUH MEDIA PEMBELAJARAN KAHOOT BERBASIS GAME BASED LEARNING TERHADAP MINAT DAN HASIL BELAJAR SISWA SMK DI BULELENG - Komang Anik Sugiani (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
The purpose of this study was to determine the effect of using kahoot as a game-based learning medium on students ' interests and learning outcomes in Interaction design subjects at SMK Negeri 1 Sukasada. This study uses a quasi-experimental quantitative approach with pretest and posttest research designs Control Group Design. The research population was students in class X Multimedia consisting of 4 classes with a total of 129 people and the sample in class X Multiemdia 2 was 32 people as the experimental class and X Multiemdia 2 with 32 people as the control class. Data collection techniques used that is form questionnaire and test. From research shows there is difference results study before and after given treatment. The results of hypothesis testing using anacova test and t-test with a significance value of 0.000 it means that sig value < 0.05 as well as pearson correlation (t) of 0.861. So that H0 is rejected and Ha is accepted. So could concluded there is influence user Kahoot as a learning medium based game-based learning against interest learning and results study participant educate as well as there is correlation Among interest and results eye study lesson chemistry at SMK Negeri 1 Sukasada.